HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN GROUNDSTROKEFOREHAND PERMAINAN TENNIS LAPANGAN PADA MAHASISWA PENJAS 2013 PEDIDIKAN OLAHRAGA FKIP UR. - Wijayanti, Ni Putu Nita; ', Rafles; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem of this resert is the lack of groundstroke forehand’s ability in tennis game of health physical education students on the year of 2013. It is suspected, because of the lack of arms and shoulders power explosion when doing groundstroke forehand. The aim of this study is to find the relationship between arms and shoulders’ power explosion with the groundstroke forehand’s ability. This is correlational study that aimed to know how big the contribution between independent and dependent variables. After that, conducted data normality test by liliefors test with significant level α = 0.05, and the result for normality test of X variable is L0maks (0,144) <Ltabel (0,173), normality test of Y variable, L0maks (0,107) <Ltable (0,173), in other words, the distribution of the data is normal. Then, continued by determining the r using product moment correlational analysis, if tresult>ttable, then the result is, there is significant relationship on it. The result of this research showed that there is a significant relationship between arms and shoulders’ power explosion with the groundstroke forehand’s ability, tresult(3,061) >rtable(1,708). So, Ho is refused and Ha is accepted. Based on the research result,the conclusion is there is significant relationship between the arms and shoulders’ power explosion with the groundstroke forehand’s ability in tennis game of health physical education students on the year of 2013.Keywords: Power Explosion, Groundstroke Forehand’s Ability